Analysis of Consumer Preference Comparison Toward Sources of Animal Protein: Application of the Theory of Planned Behavior - Angga Adi Prihananto; Anna Amalyah Agus (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze consumer behavior regarding animal-based protein consumption in Indonesia using the Theory of Planned Behavior (TPB). The research focuses on the influence of attitude, subjective norm, perceived behavioral control, and past experience on the intention to consume protein sources such as chicken, fish, eggs, and beef. A quantitative approach was employed using Partial Least Squares-Structural Equation Modeling (PLS-SEM), supported by Multigroup Analysis to examine differences across demographic groups including age, education, income, and region. The results show that all TPB constructs significantly influence consumption intention, with Past Experience emerging as the most dominant predictor. The multigroup analysis revealed a statistically significant difference only in the Subjective Norm → Behavioral Intention path based on regional residence. These findings offer practical insights for food industry stakeholders and policymakers to design more targeted strategies to promote animal protein consumption.